Upaya Ibu Rumah Tangga Yang Bekerja Dalam Mengatasi Work-Family Conflict - Dheniya Fadhila Hidayat; Moh. Amin Tohari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Working mother in dual roles will create new problems, namely work-family conflict. Work-family conflict is an unequal role conflict between work and family. The aim of this research is to find out and analyze working mother in overcoming work- family conflict. This research uses a qualitative approach with descriptive method. The data collection techniques used were observation, interviews and documentation. The results of this research show that the work-family conflicts experienced by working mother as staff of the RPTRA Asthabrata, are time-based conflict, strain-based conflict and behavior-based conflict. The imbalance in the roles carried out has an impact on the lives of working mother, namely limited time with the family, decreased physical health and concentration levels, as well as the psychological pressure they experience. Efforts made to overcome work-family conflict are problem focused coping, emotion focused coping and time management.